2020
DOI: 10.1097/md.0000000000023776
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of a quality improvement program on the quality and timeliness of discharge documents

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Troude et al showed improvement of both completeness and timeliness of discharge documentation after educating physicians and after the introduction of a fixed-format discharge letter with automatically generated fields by the EHR system. However, discharge medications and treatments were still only present in 44% of letters after completion of the intervention and these were not assessed qualitatively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Troude et al showed improvement of both completeness and timeliness of discharge documentation after educating physicians and after the introduction of a fixed-format discharge letter with automatically generated fields by the EHR system. However, discharge medications and treatments were still only present in 44% of letters after completion of the intervention and these were not assessed qualitatively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%